2015
DOI: 10.4269/ajtmh.15-0189
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mining and Human Immunodeficiency Virus Infection Among Patients Admitted for Retreatment of Tuberculosis in Northern Tanzania

Abstract: Abstract. In tuberculosis (TB)-prevalent settings, patients admitted for retreatment of TB may account for a high burden of poor treatment outcome. We performed a retrospective cohort study to characterize retreatment patients and outcomes at a TB referral hospital in northern Tanzania. From 2009 to 2013, 185 patients began a retreatment regimen, the majority for relapse after prior treatment completion. Men accounted for an unexpected majority (88%), 36 (20%) were human immunodeficiency virus (HIV) infected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
7
2
Order By: Relevance
“…We found that when mortality occurred, it was early in RT-TB therapy. While one study in Tanzanian RT-TB patients found 6.5% mortality in the first two months [13], we observed over 10% mortality within the first fifteen days of therapy. This high early mortality rate likely reflects late advanced disease presentations.…”
Section: Discussioncontrasting
confidence: 80%
“…We found that when mortality occurred, it was early in RT-TB therapy. While one study in Tanzanian RT-TB patients found 6.5% mortality in the first two months [13], we observed over 10% mortality within the first fifteen days of therapy. This high early mortality rate likely reflects late advanced disease presentations.…”
Section: Discussioncontrasting
confidence: 80%
“…The standard WHO recommended retreatment regimen (category II) for PTB is an economic and TPR, true-positive rate (sensitivity); TNR, true-negative rate (specificity); PPV, positive predictive value; NPV, negative predictive value. efficient regimen [24][25][26]. However, in past two decades, the collaborative researches were conducted in many countries have provided a lot of evidence that patients ultimately failed with standard retreatment regimen [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The standard WHO recommended retreatment regimen (category II) for PTB is an economic and efficient regimen [2426]. However, in past two decades, the collaborative researches were conducted in many countries have provided a lot of evidence that patients ultimately failed with standard retreatment regimen [27–32].…”
Section: Discussionmentioning
confidence: 99%
“…[4,5,9] Small-scale miners have relatively high risk of getting TB as a result of inadequate ventilation, significant exposure to respirable crystalline silica, HIV infection, in some cases poor nutrition and alcohol abuse. [6,10] Tuberculosis transmission is favoured in poorly ventilated, dark and humid environment as is the case in most of the small-scale mining pits. As miners carry a huge TB prevalence, they also pose high risk to the surrounding communities they come into contact with.…”
Section: Introductionmentioning
confidence: 99%
“…Locally at Mererani mines, the prevalence of TB among tanzanite miners has been reported to be well higher compared to the general population. [10] The SSM are generally all men, with no standard time of the daily working shifts, almost all don't use standard personal protective equipments and just a few will use locally improvised nose and mouth protective cloths while working. [11] This study aimed to determine the current prevalence of TB among the mining communities in Mererani, situated in Simanjiro District, northern Tanzania and assess factors associated with TB.…”
Section: Introductionmentioning
confidence: 99%